The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1214/aos/1013699998
|View full text |Cite
|
Sign up to set email alerts
|

The control of the false discovery rate in multiple testing under dependency

Abstract: Benjamini and Hochberg suggest that the false discovery rate may be the appropriate error rate to control in many applied multiple testing problems. A simple procedure was given there as an FDR controlling procedure for independent test statistics and was shown to be much more powerful than comparable procedures which control the traditional familywise error rate. We prove that this same procedure also controls the false discovery rate when the test statistics have positive regression dependency on each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
3,449
1
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 8,295 publications
(3,674 citation statements)
references
References 36 publications
25
3,449
1
7
Order By: Relevance
“…Analysis of allele frequencies (GENEPOP V4.0.7, Rousset 2008) revealed that one locus (WSl03) showed significant deviation from Hardy-Weinberg Equilibrium. Neither Bonferroni correction, or the less conservative B-Y FDR method (Benjamini and Yekutieli 2001;Narum 2006), altered this result. There was no significant probability of null-alleles (P [ 0.05) (MICRO-CHECKER, Van Oosterhout et al 2004).…”
Section: Methodsmentioning
confidence: 84%
“…Analysis of allele frequencies (GENEPOP V4.0.7, Rousset 2008) revealed that one locus (WSl03) showed significant deviation from Hardy-Weinberg Equilibrium. Neither Bonferroni correction, or the less conservative B-Y FDR method (Benjamini and Yekutieli 2001;Narum 2006), altered this result. There was no significant probability of null-alleles (P [ 0.05) (MICRO-CHECKER, Van Oosterhout et al 2004).…”
Section: Methodsmentioning
confidence: 84%
“…The fixed effects were 'day of treatment' (from the first to the third night of treatment), 'weather' (in this analysis stormy days were pooled with rainy days because they were restricted to a single cycle) and 'temperature at sunrise'. We ran one-tailed tests because the predicted effect is only in one direction using the pbkrtest package (Halekoh & Højsgaard, 2014); we adjusted P values for multiple testing (eight tests) using the false discovery rate (Benjamini & Yekutieli, 2001). For the robin, for which we found evidence for a carryover effect during the illuminated phase, we evaluated whether it was similar in both years by adding the interaction between 'day of treatment' and 'year' in the model.…”
Section: Discussionmentioning
confidence: 99%
“…The level of significance (0.05) was adjusted following Benjamini and Yekutieli (2001), and the level of significance resulting was 0.1625; the program used was SPSS 15.0 for Windows.…”
Section: Statistical Treatmentmentioning
confidence: 99%